A comprehensive study on the extraction of transition metals from waste random access memory using acetic acid as a chelating solvent. Issue 6 (December 2022) - Preetam, Amrita; Modak, Arindam; Jadhao, Prashant Ram; Naik, S.N.; Pant, K.K.; Kumar, Vivek
Abstract: The reduced lifespan of electrical and electronic equipment results in the generation of electronic waste (e-waste), one of the fastest-growing solid waste streams. A systematic and practical approach is needed for the sound management of e-waste and metal recovery. We report an effective and comprehensive study for metal extraction from waste random access memory using acetic acid as a chelating solvent. Under the optimized conditions, Cu, Pb, Zn, and Ni extraction was 97.5%, 88.2%, 79.3%, and 83.7%, respectively. Subsequently, the kinetic study revealed that the diffusion-controlled mechanism governs the metal extraction. The calculated activation energy for Cu, Pb, Zn, and Ni are 11.3, 12.6, 17.6, and 13.3 kJ/mol, respectively, which indicates Cu-extraction could be more favourable than the rest of the metals. Furthermore, the metal leached salt was recovered from the leached solution and was thoroughly characterized to understand the nature of the compound formed and the corresponding leaching mechanism. It was observed that the leached salt could be comparable with standard copper acetate, revealing the acetic acid's ligation property. Finally, the Cu-content in the cathode was recovered as 92.7 wt% from the leached solution using the electrowinning process. We believe, our contribution can be a paradigm for promoting the effective extraction of transition metals from waste random access memory. Graphical Abstract: ga1 Highlights: Pre-treatment of WRAM using supercritical ethanol results in metal-rich fraction. Metal extraction was performed from metal-rich fractions using CH3 COOH and H2 O2 . The method effectively extracted 97.5% Cu, 88.2% Pb, 83.7% Ni, and 79.3% Zn. Kinetic study revealed the extraction was controlled by internal diffusion. Recovery of Cu with 92.7 wt% purity was achieved via electrowinning.